Effect of Nectar Composition on Bee Attraction for Onion Seed Production - Soto Vargas, Verónica Carolina (2015)
Onion is the second most cultivated vegetable crop in the world. Two types of onion varieties are usually grown around the world; open pollinated (OP) and first generation (F1) hybrids. Honey bees are the main pollinators of onion seed production, but owing to low attractiveness of flowers, pollination is often inadequate. Pollination problems result in low seed yields. Field observations indicate that F1 hybrid seed yields are much lower than open-pollinated varieties seed yields, with a decrease of up to 60%. Nectar is the most important floral reward offered by plants. Floral nectar composition has been studied as the potential cause of bee preferences in many species, among them onion. Nectar usually does not repel bees, but some nectar may be less attractive than nectar of competing flowers. Honeybees have distaste for onion flowers and avoid visiting them. Frequently, onion nectar potassium concentration and nectar sucrose concentration have been mentioned as potential causes of bee unattractiveness. Also, minor components of nectar such as phenols, amino acids, proteins, organosulfur compounds and alkaloids might directly affect bee foraging. There are differences in the chemical composition of nectar and floral morphology between open pollinated and F1 Hybrids and also within F1 Hybrids. These differences are correlated with the number of visits and seed yield. Therefore, it would be possible to select indirectly the most promising seed production lines analyzing nectar or floral morphological characters.